Development of Kelulut (Trigona sp) Cultivation Business - Nuwa, Nuwa; Rotinsulu, Johanna Maria; Toni, Hendra; Jemi, Renhart (Universitas Lambung Mangkurat, 2025)
Tumbang Nusa Village, Jabiren District, Pulang Pisau Regency, Central Kalimantan community groups have been formed into the Nusa Sehati Peat Ecosystem Protection Control Working Team (TKPPEG). They serve as partners in managing peat ecosystem protection. Alongside peat ecosystem conservation, improving the community's economy is essential. One initiative is the cultivation of kelulut bees (Trigona Sp), which has not been optimally implemented, particularly in technical beekeeping and honey marketing. Thus, the kelulut cultivation business was developed through the Community Empowerment Lecturer Program (PDPPM) at the University of Palangka Raya. The program's objectives include increasing kelulut honey production, enhancing online marketing, and creating product branding. The implementation involved training, field practice, and mentoring. As a result, lulus bees cultivated with a two-week harvest cycle produced approximately 14.5 liters of honey. Branding efforts allowed Kelulut Honey to compete better in the market, and marketing was conducted via WhatsApp, Instagram, and Facebook. In conclusion, community partners succeeded in cultivating kelulut honeybees, created branding, and adopted online marketing techniques. Their beekeeping skills improved, and they learned the importance of logos, packaging, and product narratives. This extended their market reach, increased sales, and allowed access to non-local consumers.